Microtubule-dependent endosomal sorting of clathrin-independent cargo by Hook1 - Maldonado-Báez, Lymarie (The Rockefeller University Press, 2013)
Many plasma membrane (PM) proteins enter cells nonselectively through clathrin-independent endocytosis (CIE). Here, we present evidence that cytoplasmic sequences in three CIE cargo proteins—CD44, CD98, and CD147—were responsible for the rapid sorting of these proteins into endosomal tubules away from endosomes associated with early endosomal antigen 1 (EEA1). We found that Hook1, a microtubule- and cargo-tethering protein, recognized the cytoplasmic tail of CD147 to help sort it and CD98 into Rab22a-dependent tubules associated with recycling. Depletion of Hook1 from cells altered trafficking of CD44, CD98, and CD147 toward EEA1 compartments and impaired the recycling of CD98 back to the PM. In contrast, another CIE cargo protein, major histocompatibility complex class I, which normally traffics to EEA1 compartments, was not affected by depletion of Hook1. Loss of Hook1 also led to an inhibition of cell spreading, implicating a role for Hook1 sorting of specific CIE cargo proteins away from bulk membrane and back to the PM.